Evaluation of Lead Time for Non Concoacted Patiens Electric Electronic Prescription at The Pharmaceutical Installation Medica Citratama Tasikmalaya Hospital - Fauzi, Muhammad Imam; Ramdhani, Susan Sintia; Kurniasih, Nia; Harun, Nurhidayati (Ad-Dawaa : Journal of Pharmacy, 2024)
E-prescribing is a recipe that is transmitted using electronic media to replace handwriting, which connects various information between doctors, electronic prescription devices, and pharmacies both directly and indirectly. Electronic prescribing is a part of technology in which other medical can write electronic prescriptions and can send it to the intended pharmacy computer section in an eprescribing network, directly from the doctor's office / place of care. Utilization of an electronic system that was originally only aimed at saving paper (paperless), but in its development many benefits are obtained from this system. Among other things to prevent reading errors in recipes, errors in reading the rules of use and shorten service time. This research was conducted by collecting data simultaneously for 10 days from July 6, 2020 to July 17, 2020. The data taken were 260 outpatient non-concocted electronic prescriptions. The leading time for outpatient non-concocted electronic prescription at the street Pharmaceutical Installation Medika Citratama Tasikmalaya Hospital services is 25.19 minutes. This has fulfilled the Decree of the Minister of Health No.129/Menkes/SK/II/2008, namely the leading time for concoctions is less than 60 minutes and the waiting time for non-concoctions is less than 30 minute.